2023
DOI: 10.16899/jcm.1315131
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-Like Receptor 9 Expression With Prognosis in Breast Carcinoma

Abstract: Aim: Breast cancer (BC) is a common malignancy in women. Some molecules including TLR9 are still under investigation as potential prognostic factors in BC. In the present study, we aimed to determine the relation between TLR9 expression and clinicopathological prognostic parameters and survival in BC. Materials and methods: One hundred and thirty nine patients diagnosed as BC included the present study. Immuno-reactivity scoring (IRS) system was used to reveal the tissue TLR9 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…It seems that the anti- or protumor effects of TLRs depend on the TLR is question, the cancer type and the immune cells infiltrating the tumor [ 23 ]. A recent 2023 study by Çelik et al on breast cancer found high TLR9 expression to associate with invasive carcinoma and low expression to associate with increased overall survival [ 32 ]. TLR7 and TLR8 activation in non-small cell lung cancer induced survival of cancer cell lines and increased cancer cell chemoresistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the anti- or protumor effects of TLRs depend on the TLR is question, the cancer type and the immune cells infiltrating the tumor [ 23 ]. A recent 2023 study by Çelik et al on breast cancer found high TLR9 expression to associate with invasive carcinoma and low expression to associate with increased overall survival [ 32 ]. TLR7 and TLR8 activation in non-small cell lung cancer induced survival of cancer cell lines and increased cancer cell chemoresistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%